Sex ratios and life tables: Historical demography of the age at which women outnumber men in seven countries, 1850–2016. Issue 4 (2nd October 2019) - Hollingshaus, Mike; Utz, Rebecca; Schacht, Ryan; Smith, Ken R.
Abstract: The male/female sex ratio (SR) and its age-specific patterns vary considerably across time and place. The SR generally begins male-biased at birth and becomes female-biased later in life, but this relationship should respond to historical trends and events. Temporal trends in SRs remain largely unstudied and formal demographic relationships are not well defined. We (1) define SRs in a life table framework, (2) estimate the age at which the number of males and females achieves parity—the sex ratio crossover (SRX)—using basic life table methods, and (3) explore historical and international patterns in these trends. Using publicly-available data from the Human Mortality Database, we construct SR and SRX measures from period and cohort life tables. Analyses explore temporal patterns for seven countries in different global regions since 1850. Overall temporal trends show the SRX advancing to older ages. The SRX also appears to respond to historical events such as wars and epidemics. The measure is simple to construct from life table data, and provides additional insight into the historical context of gender dynamics.